2007
DOI: 10.1007/s10661-007-9697-z
|View full text |Cite
|
Sign up to set email alerts
|

Alternative soil quality indices for evaluating the effect of intensive cropping, fertilisation and manuring for 31 years in the semi-arid soils of India

Abstract: Soil quality assessment provides a tool for evaluating the sustainability of alternative soil management practices. Our objective was to develop the most sensitive soil quality index for evaluating fertilizer, farm yard manure (FYM), and crop management practices on a semiarid Inceptisol in India. Soil indicators and crop yield data from a long-term (31 years) fertilizer, manure, and crop rotation (maize, wheat, cowpea, pearl millet) study at the Indian Agricultural Research Institute (IARI) near New Delhi wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
211
1
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(233 citation statements)
references
References 32 publications
5
211
1
16
Order By: Relevance
“…According to the method described by Bastida et al (2006) and Masto et al (2008), a soil quality index (SQI) was established. A principal component analysis (PCA) was used to select the appropriate indices and their weighting factors.…”
Section: Soil Quality Index (Sqi)mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the method described by Bastida et al (2006) and Masto et al (2008), a soil quality index (SQI) was established. A principal component analysis (PCA) was used to select the appropriate indices and their weighting factors.…”
Section: Soil Quality Index (Sqi)mentioning
confidence: 99%
“…If the high factor variables were not correlated with each other, then each was considered important and thus retained. Among wellcorrelated parameters, the parameter with the highest factor loading was chosen for the SQI (Bastida et al 2006;Masto et al 2008;Sinha et al 2009;C. Zhang et al 2011b).…”
Section: Soil Quality Index (Sqi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in these soil properties is interconnected to the improper use of inorganic fertilizer and lack of organic fertilization, practices that are now widespread in the most intensive agriculture in developing countries [2]. For instance, repeated-application of urea under crop production and soil fertility improvement program is not only causing nutrient imbalances, but also negatively affecting the physical and biological properties of the soils [3].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in chemical and microbial soil characteristics were observed in other studies of organic farming, mainly with regard to microbial biomass, organic matter sequestration and nutrient retention, depending on the quantity and quality of the applied manure, organic supplementation, and crop rotation with legumes (Graham & Haynes, 2006;Marriott & Wander, 2006;Flieβbach et al, 2007;Probst et al, 2008). In India, data from a field study of soil quality as related to fertilizer and manure application for 31 years showed the highest quality indices in manuretreated plots (Masto et al, 2007).…”
Section: Organic Carbon and Microbial And Water Content Of The Soilmentioning
confidence: 87%